The Designing Marketing Content as a Strategy to Strengthen MSME Performance Optimization - Erlita Khrisinta Dewi; Nessa Ananda; Monanda Wandita Rini; Dahliyah Hayati (Bakti Cendana, 2026)
This community service activity aims to provide education on the importance of attractive marketing content for improving the Yama Roti Depok West Java business. The results of identifying problems in the field found that Yama Roti still sells products in a simple way so that consumers are less interested in the bread and cake products being sold. Knowledge of social media as a promotional medium is also limited, which has an impact on Yama Roti's income. The community service program was carried out through site visits to the business location and implemented in the form of training, mentoring, and consultation on marketing content development. Through this activity, it is hoped that it can provide new insight and understanding to owners and employees about the importance of marketing content for product marketing. This activity can have a positive impact on increasing marketing of Yama Roti. Business owners and employees will gradually create more interesting and creative marketing content. However, this has not been done consistently so a lot of assistance is still needed so that the results of the extension activities can be carried out well.